Operating systems : internals and design principles - Stallings, William (Boston, Massachusetts : Pearson, 2015)
Operating Systems: Internals and Design Principles is intended for use in a one- or two-semester undergraduate course in operating systems for computer science, computer engineering, and electrical engineering majors. It also serves as a useful reference for programmers, systems engineers, network designers and others involved in the design of computer products, information system and computer system personnel. ¿ Operating Systems provides a comprehensive and unified introduction to operating systems topics. Stallings emphasizes both design issues and fundamental principles in contemporary systems and gives readers a solid understanding of the key structures and mechanisms of operating systems. He discusses design trade-offs and the practical decisions affecting design, performance and security. The book illustrates and reinforces design concepts and ties them to real-world design choices through the use of case studies in Linux, UNIX, Android, and Windows 8.
Part 1. Background -- Chapter 1. Computer systems overview -- Chapter 2. Operating system overview -- Part 2. Processes -- Chapter 3. Process description and control -- Chapter 4. Threads -- Chapter 5. Concurrency : Mutual exclusion and synchronization -- Chapter 6. Concurrency : Deadlock and starvation -- Part 3. Memory -- Chapter 7. Memory management -- Chapter 8. Virtual memory -- Part 4. Scheduling -- Chapter 9. Uniprocessor scheduling -- Chapter 10. Multiprocessor, multicore, and real-time scheduling -- Part 5. Input/output and files -- Chapter 11. I/O Management and disk scheduling -- Chapter 12. File management -- Part 6. Embedded systems -- Chapter 13. Embedded operating systems -- Chapter 14. Virtual machines -- Chapter 15. Operating system security -- Chapter 16. Distributed processing, client/server, and cluster -- Chapter 17. Network protocols -- Chapter 18. Distributed process management -- Chapter 19. Overview of probability and stochastic processes -- Chapter 20. Queueing analysis.
Includes bibliographical references and index.
Keywords: OPERATING SYSTEMS (COMPUTERS)